1998
DOI: 10.1002/(sici)1096-8644(199809)107:1<25::aid-ajpa3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Dental defects of congenital syphilis

Abstract: Diagnosis of the congenital form of syphilis is an important part of the palaeopathology of this disease. In theory, there are clear clinical signs to be found in the long bones and teeth, but it has rarely been possible to recognise the latter with a confidence in archaeological material, partly because the original descriptions of the dental deformities are sometimes contradictory and partly because it is nowadays difficult to find reference specimens in museums. This article describes two such specimens whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 29 publications
0
90
0
2
Order By: Relevance
“…A differential diagnosis was established that included congenital treponematosis, hypoplastic amelogenesis imperfecta and cuspal enamel hypoplasia. Dental characteristics of the molars in congenital venereal disease include an irregular surface with a honeycomb pattern, undefined cusps and dome-shaped teeth known as Moon's molar (Cruickshank, 1939;Hillson et al, 1998). Congenital treponemal disease seems to be a likely cause of condition, because treponematosis had been encountered in adults of the study sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A differential diagnosis was established that included congenital treponematosis, hypoplastic amelogenesis imperfecta and cuspal enamel hypoplasia. Dental characteristics of the molars in congenital venereal disease include an irregular surface with a honeycomb pattern, undefined cusps and dome-shaped teeth known as Moon's molar (Cruickshank, 1939;Hillson et al, 1998). Congenital treponemal disease seems to be a likely cause of condition, because treponematosis had been encountered in adults of the study sample.…”
Section: Resultsmentioning
confidence: 99%
“…Enamel hypoplasia serves as an indication that the presence of acute episodes of disease or malnutrition compromised the health of the individual, subsequently causing a disturbance in the process of enamel formation during childhood (Goodman & Rose, 1991;Hillson, 2000). Specific diseases such as treponematosis may affect the normal development of teeth, leading to a disruption in enamel formation (Hillson et al, 1998). It has also been suggested that vitamin D deficiency may cause poor mineralisation of enamel.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, even within the clinical scenario, the disease is so diverse (la grande simulatrice) that no single criterion can be independently applied for a clinical diagnosis and the actual definite decision can only be provided via serological / molecular testing, which, however, is not available in archaeological / anthropological samples [6,7,10]. In addition, HS may also be significant for the definite establishment of the presence of congenital syphilis in the pre-Columbian ancient Greek world and the Old World in general, as well as for the differential diagnosis between syphilis and other variants of treponemal / spirochete infections [2,3,11,28]. A thorough osteoarcheological study of the specimens at the Museum of London is very likely to yield an answer to this hypothesis.…”
Section: Resultsmentioning
confidence: 91%
“…This observation is also supported by the inclusion of the criterion in several major reviews of disease clinical diagnosis [4,5,26]. The additional fact that dental stigmata of the disease, such as Hutchinson's incisors and mulberry molars, are only observed in about 30% of all patients [2,11,27], allow us to advocate evaluating the clavicle sign in osteoarcheological studies, especially when cranial data evaluation is missing or remains inconclusive. In fact, even within the clinical scenario, the disease is so diverse (la grande simulatrice) that no single criterion can be independently applied for a clinical diagnosis and the actual definite decision can only be provided via serological / molecular testing, which, however, is not available in archaeological / anthropological samples [6,7,10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation